Antimicrobial peptide preventing beer spoilage - Kavanagh, Joanne Denise (Trinity College (Dublin, Ireland). Department of Microbiology, 2012)
Beer spoilage micro-organisms (BSMs) are a common threat to Master Brewers worldwide. Numerous studies have been carried out to date to overcome this problem, yet the most common preventative measure is the addition of chemical preservatives to the beverage. The aim of the research outlined in this thesis was to generate a series of Saccharomyces yeast strains with antimicrobial ability to minimize or eliminate beer spoilage micro-organisms without affecting the fermentation process. The human defensin, HβD-3, was chosen in this study due to its broad antimicrobial spectrum and nutraceutic potential. HβD-3 was cloned into Saccharomyces cerevisiae and Saccharomyces pastorianus on low and high copy number plasmids, under the control of a variety of gene promoters such as the inducible galactokinase (GAL1) promoter, the inducible a-glucosidase (AGT1) promoter, the constitutive translational elongation factor EF-1 alpha (TEF1) promoter and the constitutive phosphoglycerate kinase (PGKI) promoter. HβD-3 was also integrated directly into the genome of S. pastorianus.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin